1980
DOI: 10.1111/j.1469-8137.1980.tb04433.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Vesicular‐arbuscular Mycorrhizas in Increasing Growth and Phosphorus Uptake of Subterranean Clover From Phosphorus Sources of Different Solubilities

Abstract: SUMMARYThe effect of inoculation with a VA mycorrhizal fungus on growth and phosphorus uptake of subterranean clover was examined using three phosphorus sources with different solubilities. Mycorrhizas markedly increased growth and phosphorus content of tops at intermediate rates of phosphorus application for all sources., . , , w .. The effectiveness of phosphorus for plant growth for mycorrhizal plants relative to nonmycorrhizal plants was the same for a water soluble source (superphosphate) and two insolubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…However, in many others (e.g. in the nitrogen studies mentioned above) mycorrhizal infection has little effect on growth of plants, including subterranean clover, when supplies of phosphate in soil are high and no longer limiting (see, for example, Daft and Nicolson, 1966;Hall, Scott and Johnstone, 1977;Pairunan, Robson and Abbott, 1980). It is possible that, under these circumstances, differences in inflow between mycorrhizal and uninfected plants might no longer be apparent.…”
Section: Introductionmentioning
confidence: 99%
“…However, in many others (e.g. in the nitrogen studies mentioned above) mycorrhizal infection has little effect on growth of plants, including subterranean clover, when supplies of phosphate in soil are high and no longer limiting (see, for example, Daft and Nicolson, 1966;Hall, Scott and Johnstone, 1977;Pairunan, Robson and Abbott, 1980). It is possible that, under these circumstances, differences in inflow between mycorrhizal and uninfected plants might no longer be apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Such curves have been produced routinely for investigations of the physiology of growth responses in vesicular-arbuscular mycorrhizas (Pairunan, Robson & Abbott, 1980;Stribley, Tinker & Snellgrove, 1980). They typically show a growth response to mycorrhizal infection only at low to medium soil P concentrations.…”
Section: Introduction Of Host Phosphate Have Been Shown Followingmentioning
confidence: 99%
“…^"^ investigations (Mosse, 1973a(Mosse, , b, 1986Hall,, Scott & Johnstone, 1977;Menge el al., (1978): Soil disturbance can reduce both mycorrhizal Pairunan, Robson & Abbott (1980); Jacquelinetcolonization and P absorption in maize (Evans & Jeanmougin, Gianinazzi & Gianinazzi-Pearson, Miller, 1988;Fairchild & Miller, 1988) in soils from 1986; Habte & Manjunath, 1987; Daniels Hetrick, long term zero-till plots at relatively low soil P levels Hetrick & Bloom, 1984) have shown that plant (XaHCOj-extractable soil test P of 10-20 ppm). At growth responses to mycorrhizas are inconsistent higher soil P levels the effects of mycorrhizas on P when examined over a range of soil P status and plant absorption and plant growth are usually less pro-P nutrition.…”
Section: Introductionmentioning
confidence: 99%